52 global reflections : a pilgrim's travel memoir - Weller, Susie Leonard ([Tools for Transformation], 2025)
Travelers need a compass to find their bearings. Discover why outward travels often mirror your inner journey of transformation. Susie shares insights from Celtic spirituality and the Compass Rose while walking labyrinths around the globe. Experience personal growth as you contemplate how endpoints can nurture new beginnings with 150 reflection questions for journaling or discussion. As a "failure to thrive" infant, Susie began her travels at three months old when her parents drove her 300 miles to receive nurturing support from relatives. She started her international journeys at 12, living with a family she had never met in Mexico, and at 24, she embarked on a two-month solo adventure from Northern Ireland to Greece. Review the four main "seasons" and developmental stages to understand why certain themes often recur throughout life, prompting you to address unresolved issues. Gain a deeper understanding of the aspects of your Hero's Pilgrimage as you embark on an "armchair" trek through her spiritual autobiography and travel memoir. Explore 52 global locations across 34 countries, from Alaska to Australia. Enjoy new perspectives as you vicariously walk with her along the Portuguese Camino and in her other journeys by car, bus, train, plane, ferry, snorkeling, kayaking, hot air ballooning, and even camel riding. Be inspired, both politically and spiritually, to serve our world as a global citizen. Susie integrates her Bachelor's degrees in Communication and Religious Studies with a Master's Degree in Pastoral. Ministry, a Certificate in Recognizing and Healing the Wounds of Spiritual Abuse and Religious Trauma, and training as a Life and Spiritual Coach to support your pilgrimage journey.